2015
DOI: 10.32607/20758251-2015-7-3-48-54
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nucleic Acids in Urine: Sources, Structure, Diagnostic Potential

Abstract: Cell-free nucleic acids (cfNA) may reach the urine through cell necrosis or apoptosis, active secretion of nucleic acids by healthy and tumor cells of the urinary tract, and transport of circulating nucleic acids (cir- NA) from the blood into primary urine. Even though urinary DNA and RNA are fragmented, they can be used to detect marker sequences. MicroRNAs are also of interest as diagnostic probes. The stability of cfNA in the urine is determined by their structure and packaging into supramolecular complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 82 publications
2
82
1
2
Order By: Relevance
“…To reach the bladder, miRNAs have to pass through the renal filtration system. The kidney barrier has been shown to be permeable for molecules, but only complexes smaller than 6.4 nm in diameter and with a molecular weight ≤ 70 kDa corresponding to molecules of about 100 bp in size can pass through it and enter the nephron [188] . To determine the clinical value of urinary miRNAs for serous OC, Zhou et al [135] performed a miRNA microarray and showed that only miR-30a-5p was upregulated whereas 37 miRNAs were downregulated in the urine samples of OC patients when compared to healthy controls.…”
Section: Circulating Mirnas In Metastasesmentioning
confidence: 99%
“…To reach the bladder, miRNAs have to pass through the renal filtration system. The kidney barrier has been shown to be permeable for molecules, but only complexes smaller than 6.4 nm in diameter and with a molecular weight ≤ 70 kDa corresponding to molecules of about 100 bp in size can pass through it and enter the nephron [188] . To determine the clinical value of urinary miRNAs for serous OC, Zhou et al [135] performed a miRNA microarray and showed that only miR-30a-5p was upregulated whereas 37 miRNAs were downregulated in the urine samples of OC patients when compared to healthy controls.…”
Section: Circulating Mirnas In Metastasesmentioning
confidence: 99%
“…It is perhaps surprising that all body fluids examined to date contain some levels of ex-sRNA (212), but their inclusion into vesicles (including exosomes) appears distinct in different fluids (see also section 5.4 of this review) (6, 16, 31, 172). Since the pathways of export from cells play an integral part in shaping these differences, this suggests that exporting cells in different tissues/organs (e.g.…”
Section: Origins and Compositions Of Ex-srnas Complements In Humanmentioning
confidence: 99%
“…Cell-free DNA may be released passively to the blood stream by necrotic or apoptotic cells or be secreted actively from cancer cells [32,33]. It is rapidly degraded [34] or cleared from the blood via urine excretion [35,36] and ctDNA analysis thus provides a snap-shot of the tumor.…”
Section: Potential Applications Of Ctdnamentioning
confidence: 99%